A cut‐off value for the operation time and other risk factors in terms of the infection risk for flexible ureterorenoscopy. Issue 4 (1st December 2020) - Günseren, Kadir Ömür; Demir, Aslan; Celen, Sinan; Çiçek, Mehmet Çağatay; Kılıçarslan, Hakan
Abstract: Objectives: To investigate the operation time (OT) and ureteral access sheath (UAS) usage with the infection rates and to determine a cut‐off value for OT. Methods: We retrospectively analysed the data of the patients who underwent flexible ureterorenoscopy (FURS) for renal stones larger than 20 mm between 2010 and 2019. The investigated parameters were OT, UAS using, and infection status. The data were analysed by forming two groups according to whether the OT was less than 60 minutes and more, whether the UAS was used and whether an infection occurred. In addition, independent risk factors that may affect postoperative urinary infection development were also investigated by logistic regression analysis. And, a Receiver Operating Characteristic (ROC) curve analysis was applied to determine a cut‐off value in OT terms, where infection rates increase more. Results: A total of 575 patients were enrolled in the study. The rates of the usage of UAS and infection were greater statistically in the group for longer than 60 minutes. OT was longer statistically in the infection group than in the group without infection (94.1 ± 14.2 and 68.01 ± 23.1, for groups 1 and 2, respectively, P  < .05, Table 2). OT was statistically longer in the UAS group than the unused one (79.3 ± 24.4 and 66.7 ± 22.4, for groups 1 and 2, respectively, P  < .05, Table 3). ROC analyses revealed a cut‐off point of 87.5 min for OT in terms of infection rate. Conclusion: While the infection risk increases when OT exceeds 60 minutes, FURS can be safely performed up to 87.5 minutes with 89% sensitivity and 69% specificity infection risk.